Recall what composition of functions means:
Use one function 's expression as the input of the other function.
so for the case of f(x)=7x=6 and g(x)= 5 (x+6)
we can do the following:
(fog)= f(g(x)) = f (5(x+6)) = 7 (5(x+6)) - 6 = 7 (5x + 30) - 6 = 35 x + 210 - 6 =
35 x + 204.
Now for the second composition:
(gof) = g (f(x))= g (7x-6) = 5 ((7x-6)+6) = 5 ( 7x-6+6) =5 (7x)= 35 x
Therefore these are NOT the same , one gives 35 x + 204, while the other one gives 35 x.
Now for the next question:
If fog (x) = 0 what is the solution for that?
since we found what (fog)(x) is, let's make it equal zero and solve for x:
35 x + 204 = 0
then subtracting 204 from both sides;
35 x = -204
x = -204/35
Now, is (gof)(x) = 0 then we solve for x using the expression we found above:
(gof)(x) = 35 x = 0
that means that x must be zero
x = 0/35 = 0
(fog)(x) is NOT equal to (gof) (x) for the given functions